Yield and potency of follitropin extracted from pituitary glands of zebu cattle (Bos indicus) and water buffalo (Bubalus bubalis) - MEHMOOD, A.; ANWAR, M (The Indian Journal of Animal Sciences, 2013)
Two methods were compared for follitropin extractioll from the frozen-thawed pituitary glands of zebu cattle and water buffalo. The initial extraction was made by a gradual increase in the concentration of ammonium sulphate at different levels of pH, followed by precipitation of follitropin activity either by ethanol or by acetone. Follitropin yield(g/ kg of tissue) differed nonsignificantly (cattle: 2.6 and 3.1; buffalo: 2.4 and 2.5) between species and between methods of extraction. Biological potency of the follitropin-extract also differed nonsignificantly and tanged at 88.2%Â·91.7% of standard FSH.P.